Effect of Giving Sea Salt Through Drinking Water to Broilers on the Total Plate Count of Bacteria, Coliforms, and Escherichia coli in Broiler Feces - Tifano Pratista Ramandika Nur Husodo; Ida Bagus Komang Ardana; I Made Merdana; I Gusti Ketut Suarjana (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
The gastrointestinal microbiota plays an essential role in maintaining intestinal health, immune function, and productivity in broiler chickens. The growing concern about antimicrobial resistance arising from the prolonged use of antibiotic growth promoters has spurred exploration of natural alternatives to modulate gut microbial populations. Sea salt contains various minerals, including sodium, magnesium, potassium, and calcium, which may influence intestinal microbial ecology. This study aimed to evaluate the effect of sea salt supplementation through drinking water on the Total Aerobic Bacterial Count (TABC), Coliforms, and Escherichia coli populations in broiler feces. A total of 72 CP 707 broiler chickens were assigned to four treatment groups: control without sea salt supplementation (S0), 1 g/L sea salt (S1), 2 g/L sea salt (S2), and 4 g/L sea salt (S3). Fecal samples were collected by cloacal swabbing at 0, 15, and 30 days of age. Bacterial enumeration was performed using Nutrient Agar and Eosin Methylene Blue Agar. Data were analyzed using multivariate analysis of variance (MANOVA) followed by Duncan’s Multiple Range Test. The results showed that sea salt supplementation had no significant effect on TABC, Coliform, or E. coli counts (P>0.05). In contrast, broiler age significantly affected all bacterial parameters evaluated (P<0.05). Although lower bacterial counts were numerically observed in the 1 g/L and 2 g/L treatment groups compared with the control, these differences were not statistically significant. In conclusion, sea salt supplementation through drinking water at concentrations up to 4 g/L did not significantly reduce fecal bacterial populations in broiler chickens. Age-related microbial succession had a greater influence on bacterial dynamics than sea salt supplementation.